THE CONTRIBUTION OF AN EFFORT TO COLLECT OF WOOD MANGROVE ( RHIZOPHORA , SP ) AGAINST THE TOTAL INCOME HOUSEHOLDS FISHERMEN IN BANTAN TENGAH VILLAGE BANTAN SUB-DISTRICT CITY OF BENGKALIS RIAU PROVINCE - Muhammad Suhardi; M. Ramli; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on january 2015. Its purpose to find out how large household income fishermen from an effort to collect mangrove wood, The total income households and large an effort to know the contribution of collecting of mangrove wood to the total household income fishermen. The methods was used by survey method with the determination of respondents with census.The results of this study that the indicate the magnitude of the average total household income of the fishermen of Rp 3.417.000, The average household income fishermen from the activities of an effort to collect of mangrove wood is Rp 1.352.750. The mangrove supported efforts to get a total income of fishing 25,2 % of households. Based on the criteria used in the analysis of data and the contribution of an effort to collect of mangrove wood against household income fishermen of 25,5 % ,that the classification is lower income.keyword: contribution, effort to collect of mangroves, wood income